Influence Of Regulative Pressures On Strategy Implementation In Public Secondary Schools In Selected Counties In Kenya - Mutea, Harun Kaumbuthu; Senaji, Thomas Anyanje; Rintari, Nancy Gacheri (Advances in Social Sciences Research Journal, 2021)
Preparation of strategic plans and their implementation in public secondary schools is mandatory for all schools in Kenya. However, the implementation is a challenge to the majority of the schools hence the need to investigate the factors that influence it. Being a relatively new management practice in public secondary schools, empirical studies in this area are limited. Drawing from the institutional theory, we conducted a descriptive structured self-administered questionnaire survey to determine the influence of regulative pressures on strategy implementation in public secondary schools. We further, examined the moderating effect of mimetic pressures on this relationship. We found that public secondary schools experienced moderate regulative pressures from the government to implement strategies and that through binary logistic regression model, regulative pressure significantly predicted the probability of successful strategy implementation (Wald = 13.682, df = 1, p < .001, exp (B) = 3.393). However, mimetic pressures did not significantly moderate the relation between regulative pressure and strategy implementation (Wald = .098, df = 1, p = .754 > .05, exp (B) =.737). Theoretically the study contributes to the scarce empirical literature on strategy implementation from the institutional theory perspective compared to strategy formulation. Practically, the study draws attention of stakeholders to the less investigated factors that influence strategy implementation namely: the regulative pressures. These findings have implications for government to strengthen the monitoring of public secondary schools to increase the likelihood of successful strategy implementation in public secondary schools.